Dimensi Edukatif dalam Amtsal Al Qur’an dan Kajian Perspektif Kurikulum Pendidikan Agama Islam - Roshiful Aqli Qosyim (Indonesian Journal of Humanities and Social Sciences, 2021)
The Qur'an is a normative – theoretical guide in the implementation of Islamic education. Kalam contained in the Qur'an is dass solen, which must be translated into dass sein by educators into the formulation of Islamic education that can lead to the ultimate goal of education. This study aims to reveal the amsal's concept in the Qur'an and the dimensions of education contained in the amsal of the Qur'an in terms of the Islamic Religious Education curriculum. Penelitian ini merupakan jenis penelitian kepustakaan. The results reveal that the concept of Proverbs in the Qur'an Proverbs (parables) in the Qur'an contains vague or abstract meaning explanations so that they become transparent, concrete and easy to remember. This method explains and confirms the meaning of the message. Meanwhile, from the perspective of Islamic religious education, the dimensions of Al-Qur'an Proverbs viewed from the Islamic religious education curriculum include curriculum components: Objectives, Materials, Methods, Media and Evaluation.